EFEKTIVITAS PENGGUNAAN MEDIA KARTU KATA BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN KELAS I SD NEGERI TEGALREJO III - Muslimah Dwi Nurcahyani; Heru Purnomo (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This research uses a descriptive qualitative method, where this study aims to analyze and describe the effectiveness of using picture word cards as a medium to enhance early reading skills in first-grade students at Tegalrejo III Public Elementary School. Education is a fundamental right that is crucial for the progress of human civilization, and early reading skills are a critical foundation for children's academic and social success. However, the facts show that teaching early reading in schools often still uses monotonous techniques, which results in a lack of interest and unsatisfactory learning outcomes for children. Common problems faced by children include difficulties in linking letters, syllables, simple sentences, distinguishing letters, and understanding the content of reading. One of the main factors is the lack of diversity in teaching strategies and learning media used. Therefore, this research investigates the creative use of illustrated flashcards to build a dynamic and engaging learning environment. Children's motivation, letter recognition, word spelling, and early reading skills have all been shown to improve significantly with illustrated flashcards that combine words with images. This material is also considered aesthetically pleasing and easy to understand. However, the use of this media is found to have limitations, as each card typically contains only one word. To make reading activities more challenging, it is suggested to create cards that can accommodate multiple words.